Pengaruh Persepsi Karyawan atas Praktik Corporate Social Responsibility Perusahaan terhadap Komitmen Organisasional Karyawan - Paramitha Setyoastuti; Eva Hotnaidah Saragih (Journal of Management and Business Review, 2021)
The company carries out Corporate Social Responsibility (CSR) not only to show concern and contribution to stakeholders, but also to gain competitive advantage which in the long run will improve the company's image and reputation. The majority of previous research results discuss the relationship between CSR and company financial performance, consumer behavior, or its impact on the environment. Not many have studied how employees perceive CSR and its effect on organizational commitment. This research was conducted with the aim of testing the significance of the effect of employee perceptions of internal and external CSR carried out by the company on employee organizational commitment to the organization. The study was conducted using a survey method with employees from two oil and gas companies in Jakarta one foreign privately owned and one nationally owned. From the results of three hypotheses testing based on 264 survey data obtained, it was found that partially, employee perceptions of internal CSR and external CSR by the company significantly affect employee organizational commitment to the organization. The same finding was also obtained when the two independent variables were tested simultaneously on the dependent variable. From the results of the descriptive analysis, it was found that both companies were perceived to have carried out internal CSR very well on the dimensions of Health Safety and Human Rights Instrument Development, and the dimensions of Environmental Protection for external CSR